A Novel Murine Model for Chronic Inflammatory Alveolar Bone loss - Oz, Helieh S (2009)
OBJECTIVE: Chronic inflammatory bowel disease (IBD) demonstrates some similarities of dysregulated chronic immunoinflammatory lesion of periodontitis. Trinitrobenzene sulfonic acid (TNBS) and dextran sodium sulphate (DSS) administered to rodents have been shown to elicit inflammatory responses that undermine the integrity of the gut epithelium similar to IBD in humans. The objective of this study was to evaluate the ability of these chemicals to elicit periodontal inflammation as a novel model for alveolar bone loss. METHODS: Mice were treated by oral application of TNBS 2 times/week, or with DSS in the diet over a period of 18 weeks. Alveolar bone loss was assessed on defleshed skull using morphometric measures for area of bone resorption. RESULTS: TNBS-treated animals tolerated oral administration with no clinical symptoms and gained weight similar to normal controls. In contrast, DSS exerted a systemic response including shortening of colonic tissue and liver enzyme changes. Both TNBS and DSS caused a localized action on periodontal tissues with alveolar bone loss observed in both maxilla and mandibles with progression in a time dependent manner. Bone loss was detected as early as week 7, with more severe periodontitis increasing over the 18 weeks (p<0.001). Young (7 month) and old (12 month) SCID mice were treated with TNBS for a period of 7 weeks and did not develop significant bone loss. CONCLUSIONS: These data show that oral administration of TNBS and DSS provoke alveolar bone loss in concert with the autochthonous oral microbiota.